THU0288 Fatigue and Quality of Life in Patients with Systemic Lupus Erythematosus: Comparison of Different Evaluation Tools and Questionnaires. (23rd January 2014) - Bortoluzzi, A.; Amadelli, A.; Padovan, M.; Govoni, M.
Abstract : Background: Individuals with Systemic Lupus Erythematosus (SLE) face considerable physical, psychological and social challenges. The disease has profound effects on health-related quality of life (HRQoL) as well as on other subjective parameters. Among these, fatigue is the most prevalent symptom, since it is present in up to 90 % of the SLE patients. Objectives: To assess HRQoL in adult Italian SLE patients employing a generic instrument as the Medical Outcomes Study Short Form (SF-36) and a specific questionnaire developed and validated to evaluate QoL in adult SLE patients - Italy version (LupusQoL). Finally to investigate, employing the 9-item FSS, how fatigue influences QoL. Methods: The Lupus QoL questionnaires and FSS were administered to a cohort of adult patients with SLE consecutively seen at our clinic in a time interval of four months. During the visit clinical, laboratory data and disease activity assessed with SLEDAI, were collected. To perform a control, QoL was evaluated also with SF-36. The 34 questions of Lupus QoL, divided by fields, were compared with the equivalent items of SF-36. The aspects covered by Lupus QoL are these following: field 1, physical health (questions 1-8); field 2, pain (questions 9-11); field 3, planning (questions 12-14); field 4, intimate relationships (questions 15-16); field 5, burden to others, (questions 17-19); field 6 (questions 26-30) emotional health; field 7 body image (questions 20-25) and field 8 focused on fatigue (questions 31-34). Correlation tables between LupusQoL, patient age, disease duration, disease activity and fatigue were carried out. Results: 90 SLE patients were enrolled in the study (M/F : 6/84), mean age 50 years (range 23-79), mean disease duration 166 ± 94.6 months, mean SLEDAI 3 (range 0-14). A statistically significant correlation was demonstrated between each domain of the LupusQoL and the equivalent domain of the SF-36 (P <0.00001). All domains of LupusQoL were being disadvantaged in our sample, and in particular the fields 5 and 8 were the most adversely affected. More than 75% of our patients reported fatigue, evaluated according to the FSS. Analyzing the correlation tables we observed that the patient's age affected the first 4 fields of lupusQoL (P <0.05); neither the disease duration nor the disease activity affected the quality of life (p > 0.05). Finally we observed that fatigue influenced, in a statistically significant way, all the domains of the LupusQoL. Conclusions: Our study confirms that QoL is impaired in our cohort of patients with SLE as assessed by the validated lupus-specific LupusQoL. A clinically important association between the 8 domains of the LupusQoL and the presence of fatigue has been demonstrated. The sample of our study was composed of outpatients consecutively observed with an average low disease activity and this could justify the lack of correlation between disease activity and QoL. Disclosure of Interest: None Declared